1990
DOI: 10.1007/bf02544032
|View full text |Cite
|
Sign up to set email alerts
|

Intermembrane cholesterol transfer: Role of sterol carrier proteins and phosphatidylserine

Abstract: The effect of phosphatidylserine and sterol carrier proteins on cholesterol exchange was determined using an assay not requiring separation of donor and acceptor membrane vesicles. Sterol carrier protein-2 (SCP2, also called nonspecific lipid transfer protein), but not fatty acid binding protein (FABP, also called sterol carrier protein), enhanced the initial rate of sterol exchange between neutral zwitterionic phosphatidylcholine small unilamellar vesicles (SUV) 2.3-fold. Phosphatidylserine at 10 mol% increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
28
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 33 publications
3
28
0
Order By: Relevance
“…In agreement with previous studies on the binding of fluorescently labeled PC and cholesterol analogues (Nichols et al, , 1988Schroeder et al, 1990), we have shown that nsL-TP is able to form a complex with PC. However in contrast to what was observed with PC-TP and PI-TP, this complex could not be isolated (data not shown).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In agreement with previous studies on the binding of fluorescently labeled PC and cholesterol analogues (Nichols et al, , 1988Schroeder et al, 1990), we have shown that nsL-TP is able to form a complex with PC. However in contrast to what was observed with PC-TP and PI-TP, this complex could not be isolated (data not shown).…”
Section: Discussionsupporting
confidence: 92%
“…This makes it very suitable for intrinsic t r y p tophan fluorescence measurements. Upon excitation (Aex = 280-300 nm), a broad emission spectrum is observed ranging from 300 to over 400 nm, with a maximum around 330-340 nm [see also Schroeder et al (1990)l. To assess the localization of the tryptophan residue, the tryptophan fluorescence of nsL-TP was quenched by addition of acrylamide or iodide.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The lifetime studies resolved for the first time at least two DHE domains in model membranes, one less sensitive to the aqueous than the other, and that these domains were dependent on the lipid composition, temperature, and other properties of the membrane (54,119). This possibility was further supported by model membrane studies of DHE exchange which provided kinetic evidence for the existence of multiple sterol containing domains in membranes (118,(121)(122)(123)(124). DHE was especially useful for these studies because the spontaneous exchange of DHE between model membranes was very similar to that of radiolabeled cholesterol (117).…”
mentioning
confidence: 96%